KAJIAN PARTISIPASI MASYARAKAT DALAM KEGIATAN PNPM MANDIRI DI KELURAHAN KLEAK KECAMATAN MALALAYANG KOTA MANADO - Yunius ., Wenda; Jenny ., Baroleh; Jean F. J. Timban (AGRI-SOSIOEKONOMI, 2015)
The research objective was to assess community participation in each phase of activity in the PNPM Urban at Kleak Village, Malalayang District of Manado City. The method used is qualitative method, which examines the public participation at every stage and sustainability of PNPM Urban. Informants in this study amounted to 5 people on the basis that they can represent the object under study, consisting of: Head of the village, the board of the Institute for Community Empowerment (LPM), Community Self-Supporting Agency, Project Management Team / TPK PNPM Mandiri, and community members. The results showed that people at KleakVillage participated in the implementation of each phase of activity PNPM. It is shown from the community who donated labor, materials and equipment to build their physical environment, but in contributing to the fund are indeed not all community memberwho voluntarily donate. The research conclude that in the process of planning the activities of the National Program for Community Empowerment (PNPM Urban Selfhelp) community in the Kleak Village, had participated fairly well. Kleak Village communities already participating in the implementation of PNPM it is seen from the community who donated labor, materials and equipment to build their physical environment, but in contributing to the fund are indeed some who voluntarily contribute.